Synthesis, Characterization and Catalytic Activity of UiO-66-NH2 in the Esterification of Levulinic Acid - Bravo Fuchineco, Daiana Antonella (2021)
The massive use of petroleum and its possible exhaustion are driving the current researchtrend to study alternative raw materials from biomass for organic reactions. In this context, thepresent article presents a study of the catalytic esterification of levulinic acid, a platform molecule,with ethanol. Metal-organic framework (MOF) type compounds UiO-66-NH2 have been synthesized. Zirconium was incorporated, using zirconium chloride as a metal precursor, together with 2-aminoterephthalic acid as an organic binding agent. An alternative route of synthesis was proposed using more favorable conditions from an economic and environmental point of view, replacing dimethylformamide by 50 and 75% acetone as substitute solvent. The physicochemical properties of the materials were evaluated by X-ray diffraction (XRD), Infrared Spectrometry with Fourier Transform (FTIR), scanning electron microscopy (SEM), X-ray photoelectron spectroscopy (XPS), microwave plasma atomic emission spectroscopy (MP-AES) and N2 adsorption to understand their morphology, crystalline, chemical and pore structure. The progress of the reaction was followed by gas chromatography and mass spectroscopy. The catalytic activity result of MOF25% in autoclave reactor, showed 100% of selectivity to ethyl levulinate and a turnover number (TON) of 66.18 moles of product/moles of Zr. This good catalytic performance obtained by partial solvent replacement in the synthetic material provides a more economical and eco-friendly process for ethyl levulinate generation.